2018
DOI: 10.3390/nu10050626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virgin Olive Oils Differing in Their Bioactive Compound Contents on Metabolic Syndrome and Endothelial Functional Risk Biomarkers in Healthy Adults: A Randomized Double-Blind Controlled Trial

Abstract: The aim of this study was to evaluate the effect of virgin olive oils (VOOs) enriched with phenolic compounds and triterpenes on metabolic syndrome and endothelial function biomarkers in healthy adults. The trial was a three-week randomized, crossover, controlled, double-blind, intervention study involving 58 subjects supplemented with a daily dose (30 mL) of three oils: (1) a VOO (124 ppm of phenolic compounds and 86 ppm of triterpenes); (2) an optimized VOO (OVOO) (490 ppm of phenolic compounds and 86 ppm of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 53 publications
4
40
0
Order By: Relevance
“…These observations have been confirmed by the NUTRAO-LEUM study, a randomized double-blind controlled trial, which supported the hypothesis of beneficial effects of virgin olive oils on biomarkers of endothelial dysfunction in healthy adults. This study demonstrated that administration of olive oil enriched in phenols, especially in hydroxytyrosol, other than improving plasma high-density lipoprotein (HDL) levels, ameliorates the systemic ET-1 levels [35]. These data mirror those obtained in two other clinical trials which tested the effect of polyphenol-enriched olive oils on HDL-and endothelial-related markers in hypercholesterolemic subjects.…”
Section: Nutraceutical Supplementation For Atherosclerosis Preventionsupporting
confidence: 71%
“…These observations have been confirmed by the NUTRAO-LEUM study, a randomized double-blind controlled trial, which supported the hypothesis of beneficial effects of virgin olive oils on biomarkers of endothelial dysfunction in healthy adults. This study demonstrated that administration of olive oil enriched in phenols, especially in hydroxytyrosol, other than improving plasma high-density lipoprotein (HDL) levels, ameliorates the systemic ET-1 levels [35]. These data mirror those obtained in two other clinical trials which tested the effect of polyphenol-enriched olive oils on HDL-and endothelial-related markers in hypercholesterolemic subjects.…”
Section: Nutraceutical Supplementation For Atherosclerosis Preventionsupporting
confidence: 71%
“…We also observed an increase of blood HDL concentrations after PS juice intake that was not detected within the PB condition. Recent nutrition intervention studies on polyphenol-rich foods such as olive oil [40] or dark chocolate [41] have been shown to positively affect HDL levels in humans. One possible explanation is that these polyphenol-rich foods may induce changes in the biochemical properties of the lipoprotein that contribute to its main biological function, particularly in the enhancement of the cholesterol efflux capacity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Olive oil and table olives are a major part of the traditional food in the Mediterranean Aliment Culture (MAC) [ 1 ]. Olives and olive oil have been found to naturally protect against stroke, degenerative and cardiovascular diseases as well as cancer and obesity [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Extra virgin olive oil is one of the essential sources of monoenoic fatty acids and biophenol (BP)-based bioactives [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaves contain a higher concentration of BPs with secos of 1450 mg/100 FW (fresh weight) compared to the olive fruit and oil, which have 110 mg/100 g and 23 mg/100 mL, respectively [ 9 ]. Oleuropein and ligstroside aglycones, oleacein, oleocanthal, hydroxytyrosil-elenolate, tyrosil-elenolate, oleoside-11-methyl ester, elenoic acid, hydroxytyrosol, and tyrosol are downstream pathway bioactives from oleuropein and ligstroside precursors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Oleuropein is the principal BPseco in green olive fruits, leaves, and table olives, whereas olive oil is rich in its downstream metabolites [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%